Sinergi bio-surya: Model kemitraan pengabdian masyarakat untuk transformasi limbah dapur menuju kemandirian energi - Gema Romadhona; Rum Sapundani; Itmi Hidayat Kurniawan; Tanziila Faidza Arfa; Anggito Imam Raharjo (Penamas: Journal of Community Service, 2026)
RW 06 in Purwosari Village, Baturraden Subdistrict, faces two major challenges: unmanaged daily kitchen waste that contributes to sanitation and environmental problems, and reliance on PLN electricity, which is unreliable and costly for communal needs. This article presents the design, implementation, and effectiveness of the "Bio-Solar Synergy Partnership Model," a community-based Waste-to-Product (WTP) approach that integrates an anaerobic biodigester with a solar photovoltaic (PV) system. The program employed a Participatory Action Research (PAR) method, built on active collaboration among the service team, village administrators, and local community groups. The model successfully converted an average of 50 kg/day of organic kitchen waste and generated 1 kWh of electricity per day from the PV system. Importantly, the partnership model also established a local institution, the "Independent Energy Working Group (Pokja Energi Mandiri)," which independently manages operations and maintenance. The PV system plays a critical role in ensuring the continuous operation of the blender and the biodigester control system. Overall, the Bio-Solar Synergy model proved socio-technically effective: it reduced waste, produced clean energy, and strengthened community capacity and social ownership.